Bed agglomeration during fast pyrolysis of bio-oil derived fuels in a fluidized-bed reactor. (15th November 2022) - Gao, Wenran; Zhang, Mingming; Wu, Hongwei
Graphical abstract: Highlights: Agglomeration yields of fuel blend and slurry fuels are lower than that of bio-oil. Methanol and biochar have positive effect on reducing bed agglomeration. Bed agglomeration of bio-oil derived fuels is mainly governed by tar formation. Abstract: This study investigates the bed agglomeration during fast pyrolysis of bio-oil derived fuels in a fluidized-bed reactor at 800 °C, including crude glycerol/methanol/bio-oil (CGMB) blend, bio-oil/biochar (BB) and CGMB/biochar (CGMBB) slurry fuels. The results show that the agglomeration yields of CGMB blend, as well as BB and CGMBB slurries are 13.0%, 11.2% and 8.6% respectively, which are all lower than that of bio-oil (18.8%). Investigations on the influence of methanol, CG and biochar on bed agglomeration reveal the positive effect of methanol and biochar as they both reduce the tar formation for different reasons, while CG exhibits limited influence. The tar yields of CGMB, BB and CGMBB are 8.3%, 2.1% and 2.7% respectively, which are all lower than that of bio-oil with tar yield being 16.4%. The coke yield of CGMB is 4.9% and is lower than that of bio-oil which is 7.0%, while both BB and CGMBB have a higher coke yield (10.8% and 10.1% respectively) that mainly due to the presence of biochar. The agglomeration yield due to tar formation and tar yield exhibits a positive linear correlation, while bed agglomeration due to coke formation and coke yield exhibits irrelevant relationship. This clearly suggests the bed agglomeration of bio-oil derived fuels is mainly governed by tar formation.